Huysmans et l’art du portrait - Francesca Guglielmi (Seminario di filologia francese, 2021)
Huysmans gives importance to portrait paintings. There are many descriptions of portraits in his reports of expositions and of Salons. His interest in portrait paintings plays an important role in his literary work. The characters in his work often have equivalents in art. Our study aims to analyse the presence of portrait art in the work of Huysmans and intends to show how the portraits support the character description and enrich the narrative.